Stronger Together: How GLP-1 RAs and SGLT-2 Inhibitors Revolutionize Type 2 Diabetes Treatment - Sitarek, Hanna; Tabeau, Adrianna; Prus, Joanna; Pięta, Justyna; Pawlik, Agnieszka; Dudek, Patryk; Łuczak, Klaudia; Ulicka, Wiktoria; Chudzikowski, Marcel; Prokopiuk, Agata (Journal of Education, Health and Sport, 2025)
Introduction: Type 2 diabetes affects approximately 462 million people worldwide. The condition is associated with complex pathophysiology that leads to impaired glucose regulation and the development of both macrovascular and microvascular complications. The economic burden is significant, with high treatment costs and lost productivity due to complications and premature mortality. Current guidelines recommend using glucagon-like peptide-1 (GLP-1) receptor agonists and sodium-glucose cotransporter-2 (SGLT-2) inhibitors in combination for patients at high risk for cardiovascular disease or chronic kidney disease. These treatments have been shown in multiple meta-analyses to reduce the risk of major cardiovascular events, mortality, myocardial infarction, renal failure, and severe hyperglycaemia. Purpose: This review examines the impact of combining GLP-1 receptor agonists and SGLT-2 inhibitors in patients with type 2 diabetes, with a particular focus on cardiovascular risk. Materials and methods: The review analyzed PubMed articles published in the past 10 years, including clinical studies that assessed the effects of combination therapy with GLP-1 receptor agonists and SGLT-2 inhibitors in patients with type 2 diabetes. Summary: Research indicates that the combination of GLP-1 receptor agonists and SGLT-2 inhibitors leads to improved glycaemic control, better lipid management, lower blood pressure, and reduced body weight. It also improves vascular and myocardial health markers, while reducing cardiovascular risk. Although this combination therapy benefits kidney health, certain areas remain unchanged. Considering all of this, combination therapy seems to be a promising treatment, offering greater benefits than other antidiabetic therapies.